Regulation of cytoplasmic polyadenylation can generate a bistable switch - Aslam, Naveed (BioMed Central, 2012)
BACKGROUND: Translation efficiency of certain mRNAs can be regulated through a cytoplasmic polyadenylation process at the pre-initiation phase. A translational regulator controls the polyadenylation process and this regulation depends on its posttranslational modifications e.g., phosphorylation. The cytoplasmic polyadenylation binding protein (CPEB1) is one such translational regulator, which regulates the translation of some mRNAs by binding to the cytoplasmic polyadenylation element (CPE). The cytoplasmic polyadenylation process can be turned on or off by the phosphorylation or dephosphorylation state of CPEB1. A specific example could be the regulation of Calcium/Calmodulin-dependent protein kinase II (αCaMKII) translation through the phosphorylation/dephosphorylation cycle of CPEB1. RESULT: Here, we show that CPEB1 mediated polyadenylation of αCaMKII mRNA can result in a bistable switching mechanism. The switch for regulating the polyadenylation is based on a two state model of αCaMKII and its interaction with CPEB1. Based on elementary biochemical kinetics a high dimensional system of non-linear ordinary differential equations can describe the dynamic characteristics of the polyadenylation loop. Here, we simplified this high-dimensional system into approximate lower dimension system that can provide the understanding of dynamics and fixed points of original system. These simplified equations can be used to develop analytical bifurcation diagrams without the use of complex numerical tracking algorithm, and can further give us intuition about the parameter dependence of bistability in this system. CONCLUSION: This study provides a systematic method to simplify, approximate and analyze a translation/activation based positive feedback loop. This work shows how to extract low dimensional systems that can be used to obtain analytical solutions for the fixed points of the system and to describe the dynamics of the system. The methods used here have general applicability to the formulation and analysis of many molecular networks.